Digallane with Redox-Active Diimine Ligand: Dualism of Electron-Transfer Reactions - Fedushkin, Igor L; Skatova, Alexandra A; Dodonov, Vladimir A; Chudakova, Valentina A; Bazyakina, Natalia L; Piskunov, Alexander V; Demeshko, Serhiy V; Fukin, Georgy K (Inorganic chemistry, 2014)
The reactivity of digallane (dpp-Bian)Ga–Ga(dpp-Bian) (1), which consists of redox-active ligand 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene (dpp-Bian), has been studied. The reaction of 1 with I2 proceeds via one-electron oxidation of each of two dpp-Bian ligands to a radical-anionic state and affords complex (dpp-Bian)IGa–GaI(dpp-Bian) (2). Dissolution of complex 2 in pyridine (Py) gives monomeric compound (dpp-Bian)GaI(Py) (3) as a result of a solvent-induced intramolecular electron transfer from the metal–metal bond to the dpp-Bian ligands. Treatment of compound 3 with B(C6F5)3 leads to removal of pyridine and restores compound 2. The reaction of compound 1 with 3,6-di-tert-butyl-ortho-benzoquinone (3,6-Q) proceeds with oxidation of all the redox-active centers in 1 (the Ga–Ga bond and two dpp-Bian dianions) and results in mononuclear catecholate (dpp-Bian)Ga(Cat) (4) (Cat = [3,6-Q]2–). Treatment of 4 with AgBF4 gives a mixture of [(dpp-Bian)2Ag][BF4] (5) and (dpp-Bian)GaF(Cat) (6), which both consist of neutral dpp-Bian ligands. The reduction of benzylideneacetone (BA) with 1 generates the BA radical-anions, which dimerize, affording (dpp-Bian)Ga–(BA–BA)–Ga(dpp-Bian) (7). In this case the Ga–Ga bond remains unchanged. Within 10 min at 95 °C in solution compound 7 undergoes transformation to paramagnetic complex (dpp-Bian)Ga(BA–BA) (8) and metal-free compound C36H40N2 (9). The latter is a product of intramolecular addition of the C–H bond of one of the iPr groups to the CN bond in dpp-Bian. Diamagnetic compounds 3, 5, 6, and 9 have been characterized by NMR spectroscopy, and paramagnetic complexes 2, 4, 7, and 8 by ESR spectroscopy. Molecular structures of 2–7 and 9 have been established by single-crystal X-ray analysis.